Fuzzy Logic Controlled Harmonic Suppressor in Cascaded Multilevel Inverter - Y. Lalitha Kameswari; O. Chandra Sekhar (Institute of Advanced Engineering and Science, 2016)
This paper presents an investigation of seven level cascaded H-bridge (CHB) inverter in power system for compensation of harmonics.For power quality control a Fuzzy Logic Control (FLC) giving comparatively better harmonic reduction than the conventional controllers. Harmonic distortion is the most important power quality problem stirring in multilevel inverter, the harmonics can be eliminated by an optimal selection of switching angles. A hybrid evaluation technique evaluates the obtained optimal switching angles that are attained from the fuzzy inference system as well as neural network. The proposed method will be implemented in MATLAB working platform and the harmonic elimination performance will be evaluated.